HOSPITALITY GREEN BUSINESS PRACTICES: Studi Kasus : Jaringan Hotel Hilton in Bali - I Ketut Budarma; Ni Made Rai Erawati (Universitas Triatma Mulya, 2021)
Hilton hotel chain operated in 103 countries, has a long experience in hospitality business globally. It creates international initiatives in its responsible business practices, based on the characteristics of the regions where it is located. Hilton hotel chain located in Bali has an obligation to contribute to the sustainability of the Balinese culture, nature, lifestyle and local economy development. It has practiced green tourism business models, recognized and certified by independent certification bodies. Green tourism business practices driven by the needs of clients, global and local stakeholders, global conventions, national laws and local regulations. The study examined how Hilton Hotel Chain in Bali integrates local genius and values into green tourism business practices that is by nature a global quest. This research aims at adopting green tourism business practices into curriculum, learning and teaching process. At the end, graduates of tourism colleges will possess two types of competencies, core professional and green competencies. This research deploys four methods; direct observation, focus group discussion, general stadium on green tourism business practices and questionnaire. The expected result of the research is a curriculum design integrating green tourism business practices, the application of the curriculum will result in Green Integrated Learning model.